2018
DOI: 10.1021/acsomega.8b01907
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Coumarin–Pyrazolone Probe for the Detection of Cr3+ and the Application in Living Cells

Abstract: 3-(7-(Diethylamino)-2-oxo-2H-chromen-3-yl)-1-(4-phenylthiazol-2-yl)-1H-pyrazol-5­(4H)-one (COPYR) was competently synthesized from methyl 3-(7-(diethylamino)-2-oxo-2H-chromen-3-yl)-3-oxopropanoate and 2-hydrazino-4-phenyl thiazole. The interactions of receptor COPYR with various ions were investigated through absorption and steady-state fluorescence spectral studies, respectively. The results reveal that the complexation of Cr3+ ions with COPYR results in 1:1 stoichiometry, which resulted in a quick color resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It has been demonstrated 42 that during the condensation of a salicylic aldehyde derivative with dimethyl 3-oxopentanedioate (dimethyl 1,3-acetonedicarboxylate), the reaction of two ester and methylene groups led to the formation of dicoumarinyl ketone. Subsequent studies [43][44][45][46][47][48][49][50] have shown that this reaction is applicable to the preparation of 3-oxo-3-( 2…”
Section: Synthesis Of 2h-pyrano[32-g]quinolin-2-ones Containing a Pyr...mentioning
confidence: 99%
“…It has been demonstrated 42 that during the condensation of a salicylic aldehyde derivative with dimethyl 3-oxopentanedioate (dimethyl 1,3-acetonedicarboxylate), the reaction of two ester and methylene groups led to the formation of dicoumarinyl ketone. Subsequent studies [43][44][45][46][47][48][49][50] have shown that this reaction is applicable to the preparation of 3-oxo-3-( 2…”
Section: Synthesis Of 2h-pyrano[32-g]quinolin-2-ones Containing a Pyr...mentioning
confidence: 99%
“…Coumarin derivatives have been found in various plants, which are widely used in aqueous environmental monitoring, antibacterial and antitumor medications, and others [18]. Currently, coumarin-based fluorescent probes consist essentially of Schiff bases [19][20][21][22] and biological thiols [23,24]. In particular, a few studies on the coumarinbased pyrazolone fluorescent probes have been reported [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, coumarin-based fluorescent probes consist essentially of Schiff bases [19][20][21][22] and biological thiols [23,24]. In particular, a few studies on the coumarinbased pyrazolone fluorescent probes have been reported [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, coumarin- and pyrazole-based heterocyclic scaffolds could also be used as fluorescent materials, optical brighteners, and laser dyes . Owing to their significant importance, incisive and effective synthesis of these heterocyclic moieties and their functionalization have claimed continual attention from organic chemists . In 2013, Wu and his co-workers carried out C4 alkenylation of 1,3,5-trisubstituted pyrazoles (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%